A retroviral survey of endangered Eurasian lynx (Lynx lynx) from Croatia (Veterinarski arhiv, 2021)
The feline immunodeficiency virus (FIV) and feline leukemia virus (FeLV) may cause persistent, lifelong and lethal infections in domestic and wild felids worldwide. FIV has been confirmed in most Felidae species, while FeLV infection is rare among non-domestic cats. The view that retroviruses are pathogenic in domestic cats but not in other free-ranging felid species was disproved by recent findings of retroviral pathology in several wild felids. The epidemiology of retroviral infections in felids in Croatia was only investigated in urban domestic cats, while there are no data for wild cat species. As the reintroduced Dinaric lynx (Lynx lynx) population suffers from low genetic diversity, which reduces their ability to adapt to new viral outbreaks, the health status of this lynx population is of particular concern. Two different commercial immunochromatographic assays were used for qualitative detection of FIV antibodies and FeLV antigens, while PCR was used for amplification of proviral gag and env genes in Eurasian lynx blood samples. All the 17 Eurasian lynx samples collected between 2001 and 2019 tested negative in both immunochromatographic and molecular tests. Even though our sample size was rather small, considering the fact that the population size of lynx in Croatia is estimated at 40 - 60 animals, our results can be considered representative for the population’s health status. Also, data about retroviral prevalence in Eurasian lynxes are scarce, so any new findings are very valuable. Virus mačje imunodeficijencije (FIV) i virus mačje leukemije (FeLV) mogu uzrokovati trajne, cjeloživotne i smrtne infekcije u domaćih i divljih felida širom svijeta. FIV je potvrđen u većine felida, dok je infekcija FeLV-om u domaćih mačaka rijetka. Mišljenje da su retrovirusi patogeni u domaćih mačaka, ali ne i u slobodnoživućih felida, opovrgnuto je najnovijim istraživanjima retrovirusne patologije u nekoliko divljih felida. Epidemiologija retrovirusnih infekcija u felida u Hrvatskoj istraživana je u gradskih domaćih mačaka, dok podaci za divlje mačke ne postoje. Kako populaciju reintroduciranog dinarskog risa (Lynx lynx) obilježava niska genetska raznolikost, što smanjuje mogućnost prilagodbe na nove virusne zaraze, postoji osobita zabrinutost za zdravstveno stanje ove populacije risa. U radu su upotrijebljene dvije različite komercijalne imunokromatografske pretrage za kvalitativnu detekciju protutijela na FIV i FeLV antigene, dok je PCR upotrijebljen za umnažanje provirusnih gena gag i env u uzorcima krvi euroazijskog risa. Svih 17 uzoraka euroazijskog risa, prikupljenih od 2001. do 2019., bilo je negativno i u imunokromatografskom i molekularnom testu. Iako se radi o maloj veličini uzorka, s obzirom na to da je veličina populacije risa u Hrvatskoj procijenjena na 40 – 60 jedinki, naši se uzorci mogu smatrati reprezentativnima za zdravstveni status navedene populacije. Također, malo je podataka o retrovirusnoj prevalenciji u euroazijskog risa, što novim podacima dobivenim ovim istraživanjem daje dodatnu vrijednost.